A Systematic Review of Risk Factors Associated With Distal Junctional Failure in Adult Spinal Deformity Surgery. Issue 9 (November 2021) - McDonnell, Jake M.; Ahern, Daniel P.; Wagner, Scott C.; Morrissey, Patrick B.; Kaye, Ian D.; Sebastian, Arjun S.; Butler, Joseph S.
Abstract : Background: The surgical management of adult spinal deformity (ASD) is a major surgical undertaking associated with considerable perioperative risk and a substantial complication profile. Although the natural history and risk factors associated with proximal junctional kyphosis (PJK) and proximal junctional failure are widely reported, distal junctional failure (DJF) is less well understood. Study Design: A systematic review was carried out. Objectives: The primary objective is to identify the risk factors associated with DJF. The secondary objective is to delineate the incidence rate and causative factors associated with DJF. Methods: A systematic review of articles in Medline/PubMed and The Cochrane Library databases was performed according to preferred reporting items for systematic reviews and meta-analyses guidelines. Data was collated to determine the prevalence of DJF and overall revision rates, and identify potential risk factors for development of DJF. Results: Twelve studies were included for systematic review. There were 81/2261 (3.6%) cases of DJF. Overall, DJF represented 27.3% of all revision surgeries. Anterior-posterior surgery had a reduced incidence of postoperative DJF [5.0% vs. 8.7%; P =0.08; relative risk (RR)=1.73], as did patients below 60 years of age at the time of surgery (2.9% vs. 3.9%; P =0.09; RR=1.34). There was a higher incidence of DJF among those patients who received interbody fusion (9.9% vs. 5.1%; P =0.06; RR=1.93) compared with those who did not. However, none of these findings reached statistical significance. There were significantly more rates of DJF for fusions ending on L5 compared with constructs fused to the sacrum (11.7% vs. 3.6%; P =0.02; RR=3.28). Conclusions: Cohorts 60 years and above of age at the time of surgery and patients managed with posterior-only fusion or interbody fusion have increased incidences of DJF. Fusion to L5 instead of the sacrum significantly influences DJF rates. However, the quality of available evidence is low and further high-quality studies are required to more robustly analyze the clinical, radiographic, and surgical risk factors associated with the development of DJF after ASD surgery. Abstract : Supplemental Digital Content is available in the text.